A multidisciplinary Delphi consensus on the modern definition of pruritus: sensation and disease - Ständer, Sonja; Schmelz, Martin; Lerner, Ethan; Murota, Hiroyuki; Nattkemper, Leigh; Reich, Adam; Stahl, Lea-Sophie; Yosipovitch, Gil; Weisshaar, Elke; Wiegmann, Henning; Apfelbacher, Christian; Kim, Brian S. (Journal of the European Academy of Dermatology and Venereology, 2026)
Background The definition of pruritus (synonym: itch) dates back to the 17th century and does not address the complexity of the sensation or the nature of pruritus as a disease. Objective Elaborate a new definition of pruritus comprising emotional aspects, stages and causal attributes. Methods In a pre-Delphi phase, stakeholders from pruritus-relevant global societies and patients elaborated itch definition proposals. In a Delphi phase, consensus was achieved when ≥75% of the voting participants agreed (7-9 Likert scale rating range) on a statement. Results In two Delphi rounds, two statements defining the itch sensation and nine defining chronic pruritus as a disease achieved consensus. The definition of pruritus as an unpleasant sensation commonly triggering an urge to scratch mentions that external or internal factors can trigger, worsen, or improve pruritus. Chronic pruritus is described as a symptom of diseases but also as an independent disease. The definition of chronic pruritus includes temporal, physiological, causal, and quality of life aspects. Conclusions The new definition of pruritus allows the sensation to be separated from a disease state and aims to support practical use, including communication with patients, health authorities, and other stakeholders.